2004
DOI: 10.1073/pnas.0404376101
|View full text |Cite
|
Sign up to set email alerts
|

Social supports and serotonin transporter gene moderate depression in maltreated children

Abstract: In this study, measures of the quality and availability of social supports were found to moderate risk for depression associated with a history of maltreatment and the presence of the short (s) allele of the serotonin transporter gene promoter polymorphism (5-HTTLPR). The present investigation (i) replicates research in adults showing that 5-HTTLPR variation moderates the development of depression after stress, (ii) extends the finding to children, and (iii) demonstrates the ability of social supports to furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

50
507
4
12

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 711 publications
(582 citation statements)
references
References 36 publications
50
507
4
12
Order By: Relevance
“…In addition to possible pharmacological interventions, recent research on the serotonin transporter polymorphism suggests that social support can protect even genetically vulnerable children from the negative sequelae of maltreatment. 71 As evidence for significant G Â E in predicting mental health continues to emerge, 70 both scientists and the public are becoming increasingly aware that like many developmental processes, 72 the nature of gene effects on behavior, too, is often contingent upon experience.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to possible pharmacological interventions, recent research on the serotonin transporter polymorphism suggests that social support can protect even genetically vulnerable children from the negative sequelae of maltreatment. 71 As evidence for significant G Â E in predicting mental health continues to emerge, 70 both scientists and the public are becoming increasingly aware that like many developmental processes, 72 the nature of gene effects on behavior, too, is often contingent upon experience.…”
Section: Discussionmentioning
confidence: 99%
“…48 Six studies were cross-sectional surveys. 30,31,34,37,39,41,45 One study used a combined cohort/case-control design, selecting participants with extreme scores on either environmental adversity or depression for genotyping. 40 One study examined individuals exposed to a major stressor (myocardial infarction).…”
Section: Methodsmentioning
confidence: 99%
“…41 On the other hand, Kendler and colleagues 15 found that a model with recessive s (that is with ll and ls combined) provided best fit to their data and at least one other study showed results consistent with recessive s. 34 Results from child and adolescent samples place heterozygotes intermediate but close to ll homozygotes, suggesting a predominantly recessive s effect for early-onset depression. 30,40,42 When multiple outcomes were considered within one sample, a co-dominant effect was shown for the more common outcome of alcohol abuse, but a recessive s effect was apparent for the less common illicit drug use. 43 In conclusion, the role of 5-HTTLPR heterozygosity in G Â E remains unclear.…”
Section: Allelic Variants Of 5-httlpr: L a And L G Or Rs25531mentioning
confidence: 99%
See 2 more Smart Citations